Peran PT. Ritra Cargo Indonesia Dalam Menangani Proses Penerimaan, Penyimpanan dan Pengiriman Barang - Haris Padilah; Fiki Banuaji (Majalah Ilmiah Bahari Jogja, 2021)
The purpose of this study is to discuss and examine the role of PT. Ritra Cargo Indonesia Semarang Branch in the process of receiving, storing and shipping goods, as well as problems that arise related to these logistics activities. In this case, the role of PT. Ritra Cargo Indonesia Semarang Branch in the process of receiving, storing and sending goods is very important, starting from the goods coming from the supplier and unloading goods in the warehouse, the goods are stored in the warehouse with a good and neat arrangement techniques, until the goods are loaded to be sent to the customer. From the results of the discussion, it was found that the problems related to logistics and warehousing activities were: 1). Damage, 2) The fault of Lot Number on the goods, 3) The number of goods sent to the customer from the warehouse didn’t match with the order, 4) lack of operational staff personnel, and 5) lack of Forklift Driver. From the discussion, it could be concluded that the role of PT. Ritra Cargo Indonesia Semarang Branch was very influential in the process of receiving, storing and shipping goods. Therefore, more caution and thoroughness were compulsory in the process of carrying out this maritime logistics business activity.